Salt-induced sphere-to-disk transition of octadecyltrimethylammonium bromide micelles - Swanson-Vethamuthu, M.; Feitosa, E.; Brown, W. (Amer Chemical Soc, 1998)
We have used surface tension measurements, differential scanning calorimetry (DSC), dynamic light scattering (DLS), and cryo-transmission electron microscopy (cryo-TEM) to investigate the dynamic and structural behavior of octadecyltrimethylammonium bromide (C(18)TAB) micelles in water and NaBr solution. The surface tension data for fixed C(18)TAB concentrations of 25 mM and varied NaBr additions (0-50 mM) shows that the critical micelle concentration (cmc) increases after an initial decrease at 0.5 mM NaBr. This unusual effect has been explained using results from DSC and DLS. At low salt concentrations (below ca. 25 mM) the relaxation time distribution is bimodal with a dominant fast mode due to spherical micelles. Above ca. 35 mM NaBr disklike structures are favored and the relaxation time distribution is more closely unimodal. The postulated sphere-to-disk transition is supported by cryo-TEM micrographs. A pronounced increase in the micellar effective hydrodynamic radius (R-H) is observed as the NaBr concentration is increased above about 35 mM; below 35 mM the R-H of the spherical micelles changes Little with ionic strength.